Analisis Pengaruh Kualitas Pelayanan dan Kualitas Produk Terhadap Keputusan Pembelian di Aneka Usaha Percetakan Area Printing - Gustini Gustini; Azuwandri Azuwandri; Samsul Akmal (Jurnal Adminitrasi Bisnis Nusantara, 2023)
This study aims to determine the effect of service quality and product quality on purchasing decisions partially. The sampling method is purposive sampling method with a sample of 100 respondents. The analytical method used is quantitative analysis. The results showed that partially the service quality variable had a positive and significant effect, the product quality variable had a positive and significant effect. The coefficient of determination shows that 88.8% of service quality variables and product quality affect purchasing decisions, while the remaining 11.2% is influenced by other variables not examined.